A Tribute to and in Memory - Dr David Briggs AM (1948-2024) - Mark Avery (ACHSM, 2024)
Dr. David Briggs served as the Editor-in-Chief for the APJHM for 15 years and was responsible for the formation, development and steering the professional growth and impact of this publication. David was appointed by the Australasian College of Health Service Management (ACHSM) in the second year of the journal's establishment which was introduced as the College's own applied, peer reviewed journal aimed at communicating the development and practice of the field of health management within the Asia Pacific region......